Possibilities of the use of CeBr3 scintillation detectors for the measurement of the content of radionuclides in samples for environmental monitoring. (October 2021) - Idoeta, R.; Herranz, M.; Alegría, N.; Legarda, F.
Abstract: The investigation of radioactivity in samples is an application of gamma-ray spectrometry dealing with low and very low level gamma-ray activities of different isotopes. Gamma-ray spectrometry performed in the framework of radiological environmental monitoring may be done after selective sampling processes or after a chemical purification of a sample. Both cases imply that only some specific radionuclides should contribute to the obtained spectrum. Gamma-ray spectrometry performed with medium energy resolution detectors may allow the possible distinction of their photopeaks. Therefore, a cerium bromide (CeBr3 ) detector can be particularly attractive for routine tasks in radiological environmental monitoring as it has a high efficiency, medium energy resolution and it can work at room temperature. This study describes the conditions under which a CeBr3 detector can serve for some routine analysis in radiological analysis of samples collected in the environment or collected by air-samplers in environmental radiological monitoring programmes. Highlights: Gamma-ray spectrometry is essential for the investigation of samples as part of a radiological environmental monitoring. Some scintillators show medium resolution and low background. Activity concentration analysis of 131 I, 137 Cs and Ra isotopes is possible with CeBr3 detectors. Conditions for using CeBr3 detectors as a replacement for pure germanium detectors inside laboratories will be described.